The transcriptional regulatory proteins encoded by varicella-zoster virus open reading frames (ORFs) 4 and 63, but not ORF 61, are associated with purified virus particles. - Kinchington, P R (1995)
Of the five varicella-zoster virus (VZV) open reading frames (ORFs) known to encode proteins which influence viral transcriptional events, two (ORFs 10 and 62) encode proteins associated with the tegument of virus particles, where they may function during the immediate-early events of infection. In this study, antibodies which recognize the products of the three additional VZV ORFs, ORFs 4, 61, and 63, were made and used to characterize their association with virus particles. ORF 4 encoded a 52-kDa polypeptide, and antibodies to ORF 63 reacted with polypeptides of 47 and 28 kDa. Antibodies to ORF 61 recognized heterogeneous polypeptides of 62 to 66 kDa in cells infected with a vaccinia virus recombinant expressing ORF 61 and in VZV-infected melanoma cells but reacted very weakly with polypeptides of VZV-infected human foreskin fibroblasts, suggesting that cell-specific factors were involved in ORF 61 protein accumulation. Analysis of virus particles purified from melanoma cells indicated that a 52-kDa polypeptide from ORF 4 and the 47-kDa polypeptide from ORF 63, but not any from ORF 61, were associated with virus particles. The virion proteins were likely components of the tegument, as they were not solubilized by treatment of virus with mild detergents and were completely resistant to trypsin digestion unless prior envelope solubilization was performed. The products of ORFs 4 and 63 were not found in purified VZV nucleocapsids. These results suggest that forms of the ORF 4- and ORF 63-encoded transcriptional regulatory proteins are also structural and may also have roles in the immediate-early events of infection.